Validation of a Motor Competence Assessment Tool for Children and Adolescents (KTK3+) With Normative Values for 6- to 19-Year-Olds - Coppens, Eline; Laureys, Felien; Mostaert, Mireille; D'Hondt, Eva; Deconinck, Frederik J. A.; Lenoir, Matthieu (Frontiers in Physiology, 2021)
The use of the short form of the Körperkoordinationstest für Kinder (KTK3) to evaluate children’s and adolescents’ motor competence (MC) is on its increase. When combined with a catching and throwing task, assessing eye-hand coordination (EHC), it has been shown that the different aspects of motor skills are adequately covered in one compact KTK3+ test battery, studied in children between 6 and 10 years of age. The present study aimed to validate the KTK3+ test battery and to provide contemporary MC normative values for boys and girls from 6- to 19-year-olds. A total of 2271 children and adolescents (1112 boys) participated in this study and were evaluated on the four included test items: jumping sideways (JS), moving sideways (MS), balancing backwards (BB), supplemented by an EHC task. A factor analysis with multidimensional scaling demonstrated that all these test items correlate to the same latent construct: ‘MC’. A three-way MANOVA demonstrated a significant multivariate interaction effect between sex and age group (p=0.001) as well as a multivariate main effect of sex, age group and organised sport participation (p<0.001). Boys outperformed girls on two out of the four tests (JS and EHC, p<0.005), while girls were better than boys on the BB test (p<0.005). Performance scores increased across age groups on all tests (p<0.001). Only for the BB test score, a plateau effect was noted around the age of 12 years. Children and adolescents participating in sports generally outperformed their peers, who were not involved in organised sports, on the present KTK3+ test battery. These sex, age, and sport participation effects demonstrate the validity of the test battery. Normative values are provided to evaluate MC in children and adolescents 6- to 19-year-old. The use of only four tests that are identical across all ages makes the KTK3+ test battery a practical instrument to assess and compare MC development.